PEMBELAJARAN KITAB KUNING DI PONDOK PESANTREN HIDAYATULLAH TERNATE - Faizal Bachrong (INTAJ : Jurnal Penelitian Ilmiah, 2019)
Pesantren is Islamic education institution that still be needed by the Ummah. The study of kitab kuning is an important element of it, and this generally tends to be stagnant, for various reasons. Therefore the study of the use of kitab kuning in pesantren is urgent. This research highlights the reality of kitab kuning study in boarding school, mainly Pondok Pesantren Hidayatullah Ternate. This is qualitative research in which the data collection techniques are interview, observation and study of documents and literature. The analysis of the data is qualitative description. The result of this research shows that Pondok Pesantren Hidayatullah Ternate, which was established in 1994, includes a combination between Islamic boarding school system and formal education units in the form of schools and madrasas. Basically the santri are lodged. The boarding school students are junior and senior high school students, both male and female. The male and female campuses are separated by a distance of about 1 km. They are all participated in tahfidz Alquran and ta’līm diniyyah. The books studied in this boarding school are limited to 5 books that outlined by the Central Executive, regarding Aqidah, Fikih, Tafsir, Sirah and Arabic. The study of these books uses lecture method and the santris only gather and heed without having the book.